Toxic elements in packed red blood cells from smoker donors: a risk for paediatric transfusion?. Issue 8 (17th October 2019) - Boehm, Renata; Cohen, Carolina; Pulcinelli, Rianne; Caletti, Greice; Balsan, Almeri; Nascimento, Sabrina; Rocha, Rafael; Calderon, Enrique; Saint'Pierre, Tatiana; Garcia, Solange; Sekine, Leo; Onsten, Tor; et al.
Abstract : Background and Objectives: Smokers currently have no defined restrictions for blood donation. However, cigarette smoke contains toxic substances such as carbon monoxide (CO) and trace elements that can affect the packed red blood cells (PRBCs) quality and safety of transfusion. This study evaluated the effects of smoking on the concentration of essential and trace elements and on carboxyhemoglobin (COHb) levels in PRBCs from smoker donors. Materials and Methods: A matched case–control study was conducted to compare COHb levels, determined by the CO‐oximetry method, and levels of trace (Cd, Pb, Cr, Ni, As and Hg) and essential (Ca, Mg, Cu, Fe, Mn, Mo, Se and Zn) elements evaluated by inductively coupled plasma mass spectrometry, in PRBCs from smoker ( n  = 36) and non‐smoker ( n  = 36) donors at Hospital de Clínicas de Porto Alegre, Brazil. Results: Mean COHb level was 14 times higher in the PRBCs obtained from smoker donors (5·9 [4·0–9·1] vs. 0·4 [0·2–0·8]%). Cadmium (1·0 [1·0‐1·8] μg/l vs. undetectable) and lead (27 [21–36] vs. 19 [14–26] μg/l) levels were significantly higher in the PRBCs from smokers. Moreover, except for molybdenum, levels of all essential elements were lower in smoker PRBCs. Conclusion: The PRBCs donated by smokers contain toxic elements that are probably not safe for transfusion in children. Our results might support changes in the current guidelines of blood banks to improve the transfusion safety through inclusion of inquiry about smoking in the clinical screening, labelling and reserve PRBCs from smoker donors for adults or less critical recipients.